Determinants of poor clinical outcome in patients with influenza pneumonia: A systematic review and meta-analysis - Arranz-Herrero, Javier; Presa, Jesús; Rius-Rocabert, Sergio; Utrero-Rico, Alberto; Arranz-Arija, José Ángel; Lalueza, Antonio; Escribese, María M; Ochando, Jordi; Soriano, Vicente; Nistal-Villan, Estanislao (International Journal of Infectious Diseases, 2023)
Background: The clinical burden of influenza is increasing worldwide. Aging, immunosuppression, and underlying respiratory illness are determinants of poor clinical outcomes, including greater mortality. Bacterial infections seem to be the main reason. Updated information on the role of bacterial infection as the cause of complications would be of value in improving the prognosis of patients with influenza. Methods: A systematic review and meta-analysis were performed by using the PubMed repository using keywords like: Influenza, H1N1, Streptococcus pneumoniae, bacterial coinfection, secondary coinfection, bacterial complications in pneumonia, and seasonal influenza. Only articles written in English were included in publications from 2010 to 2020. The analyses were conducted following the preferred reporting items for systematic review and meta-analyses guidelines. The results were independently validated using a TrinetX database cohort of roughly 4 million patients. Results: We included 135 studies that contained data from 48,259 patients hospitalized with influenza of any age. Bacterial infections were diagnosed in 5391 (11.2%). Streptococcus pneumoniae (30.7%) and Staphylococcus aureus (30.4%) were the most frequent microorganisms, followed by Haemophilus influenzae (7.1%) and Pseudomonas aeruginosa (5.9%). The random-effects model of the meta-analysis indicated that bacterial infections posed a 3.4-fold increased risk of death compared with influenza infection alone. Unexpectedly, asthma was protective (odds ratio 0.8). Conclusion: Bacterial infections diagnosed in 11.2% of patients with influenza increase 3.4-fold the mortality risk. S. pneumoniae, S. aureus, H. influenzae, and P. aeruginosa account for nearly 75% of the cases. Earlier diagnosis and use of antibiotics should improve outcomes in this population.
Keywords: antibiotic use; bacterial infection; influenza; prognosis; staphylococcus aureus; streptococcus pneumoniae; Scopus; JCR